Inclusive dijet cross sections in neutral current deep inelastic scattering at HERA - Abramowicz, H; Abt, I; Adamczyk, L; Adamus, M; Aggarwal, R; Antonelli, S; Antonioli, P; Antonov, A; Arneodo, M; Aushev, V; Aushev, Y; Bachynska, O; et al. (Springer-Verlag, 2010)
Single- and double-differential inclusive dijet cross sections in neutral current deep inelastic ep scattering have been measured with the ZEUS detector using an integrated luminosity of 374 pb−1. The measurement was performed at large values of the photon virtuality, Q 2, between 125 and 20 000 GeV2. The jets were reconstructed with the k T cluster algorithm in the Breit reference frame and selected by requiring their transverse energies in the Breit frame, EjetT,B, to be larger than 8 GeV. In addition, the invariant mass of the dijet system, Mjj, was required to be greater than 20 GeV. The cross sections are described by the predictions of next-to-leading-order QCD.